Crying Hegel in Art History. Issue 2 (14th March 2016) - Verstegen, Ian
Abstract : Within cultural history there is a widespread eschewal of speculative reasoning. This article notes the complicity of the general postmodern avoidance of metanarratives with Anglo-Saxon empiricism and locates the major problem facing cultural history in postmodernism's conflation of trajectories and teleologies. Any discussion of the directionality of history is imputed to be a full-blown teleology. Using previous discussions from different fields, the difference between a teleology and trajectory is defended and, after clarifying certain confusions, it is argued that trajectories, as following the working of generative mechanisms, are necessary to theorize in order to make interesting progress within the field of cultural history.